„Opierzona rewolucja” (Fledged Revolution). Reality and Fiction in a Reportage on the Soviet Union by Melchior Wańkowicz - Głuszkowski, Piotr (Porównania, 2025)
Melchior Wańkowicz had always been interested in Russia, both pre-revolutionary and Soviet. In December 1933, using the services of Inturist (Soviet organization for International Tourism), he went on a six-day trip to the Soviet Union. The result of the trip was a reportage consisting of 10 texts, in which he tried, on the basis of his own observations, to dispel numerous stereotypes about the USSR. His knowledge of the language and realities of pre-revolutionary Russia allowed him to make many interesting observations. He laid particular emphasis on the importance of people in a socialist state and how their ability to build the world of the future raised their pride. In retrospect, it is clear that Wańkowicz succumbed to Soviet propaganda.